Zero Citation in Russian Medical Science, 1990–2017 - A. V. Nemtsov; E. A. Kuznetsova-Moreva; V. V. Shein (Ekonomika Nauki)
A scientometric study of 51 research institutes of the Ministry of Health of the Russian Federation was carried out. 139,342 publications registered in the Russian Science Citation Index in 1950-2017, were the material of the study. We studied the distribution of publications by year of publication and the number of citations. The publications were divided into two groups: 1) cited one or more times (n = 65395 or 46.9%) and 2) with zero citation (n = 73946 or 53.1%). In 2001-2016 the total number of publications increases linearly (regression coefficient 721 publications or 10% per year). At the same time, the share of cited publications decreased from 72% in 2001 to 46% in 2014, and later, to 4% in 2017. During the period of the highest publication activity (2000-2013), the proportion of cited publications ranged from 17 % to 81% in different institutions (median 61%). The proportion of cited publications may be an indicator of the effectiveness of institutions.